2010
DOI: 10.1111/j.1469-8749.2009.03542.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe childhood encephalopathy with dyskinesia and prolonged cognitive disturbances: evidence for anti‐N‐methyl‐d‐aspartate receptor encephalitis

Abstract: AIM We report four cases of acquired severe encephalopathy with massive hyperkinesia, marked neurological and cognitive regression, sleep disturbance, prolonged mutism, and a remarkably delayed recovery (time to full recovery between 5 and 18mo) with an overall good outcome, and its association with anti-N-methyl-D-aspartate (anti-NMDA) receptor antibodies.METHOD We reviewed the four cases retrospectively and we also reviewed the literature. RESULTS Anti-NMDA receptor antibodies (without ovarian teratoma detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…Deficits Downloaded by [University of Sussex Library] at 13:55 22 June 2016 in attention, executive functioning, verbal fluency, and rapid naming were seen in two pediatric patients (one patient at 10 months after disease onset and the other at 21 months post-onset); the first patient showed significant improvement 22 months after onset, with many performances returning to the patient's estimated premorbid baseline (iadisernia et al, 2012). Persistent deficits in working memory and/or attention have been similarly reported in other studies (Azizyan, Albrektson, Maya, Pressman, & Moser, 2014;Dalmau et al, 2008;Poloni et al, 2010). in sum, most studies have documented persistent memory and executive deficits for adults in the chronic phase of anti-NMDA receptor encephalitis.…”
Section: Introductionsupporting
confidence: 72%
“…Deficits Downloaded by [University of Sussex Library] at 13:55 22 June 2016 in attention, executive functioning, verbal fluency, and rapid naming were seen in two pediatric patients (one patient at 10 months after disease onset and the other at 21 months post-onset); the first patient showed significant improvement 22 months after onset, with many performances returning to the patient's estimated premorbid baseline (iadisernia et al, 2012). Persistent deficits in working memory and/or attention have been similarly reported in other studies (Azizyan, Albrektson, Maya, Pressman, & Moser, 2014;Dalmau et al, 2008;Poloni et al, 2010). in sum, most studies have documented persistent memory and executive deficits for adults in the chronic phase of anti-NMDA receptor encephalitis.…”
Section: Introductionsupporting
confidence: 72%
“…16 NMDAR antagonists in animal studies cause insomnia and hyperactivity, prolonged changes in non-REM sleep, and hypoventilation. 17 In humans, NMDAR antagonists at low doses induce psychotic behavior, memory problems, and decreased response to pain. At higher doses, they can cause dissociative anesthesia, catatonic symptoms, and autonomic disruption, causing hypersalivation, cardiac arrhythmias, and hypertension.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Poloni et al reported the following recovery sequence: gradual resolution of dyskinesias followed by improvement in motor, then comprehension and expressive functions. 6 In most reports, the brain MRI is often normal or shows transient fluid attenuation inversion recovery or contrast-enhancing abnormalities involving the medial temporal lobes, basal ganglia, corpus callosum, and brainstem. The electroencephalogram reveals diffuse slowing without epileptiform discharges or disorganized activity that does not correlate with most abnormal movements.…”
Section: Discussionmentioning
confidence: 99%
“…Immune modulation through the use of immunoglobulin, corticosteroids, cyclophosphamide, plasmapheresis, and possibly rituximab are the mainstay of treatment in nonparaneoplastic encephalitis. 1,6,12,13 Individuals with ovarian teratoma are treated by tumor excision and with immunotherapy. About 75% of individuals have full or substantial regression of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation